Conditional Volatility Estimation by Conditional Quantile Autoregression - Mutunga, D. N.; Mwita, Peter N.; Muema, B. K. (HIKARI Ltd, 2014)
This paper considers the problem of estimating conditional volatility function using conditional quantile autoregression function. We estimate the interquantile autoregression range and the conditional volatility function under known distributional assumptions. The conditional volatility function estimator is found to be theoretically consistent. A small simulation study ascertains that the Volatility Estimator is consistent. Mathematics Subject Classification: 62G05; 62M1
Keywords: Quantile; InterQuantile; Autoregression